Het geheim kunst / : Lineart/08 : gids voor de kunstverzamelaar - Derycke, Luc ; Delrue, Ronny ; Van Kerckhoven, Anne-Mie ; Meuris, Wesley ; De Smet, Gery ; Vandekerckhove, Hans; Mels, Mieke; Lybeer, Charlotte (Tielt, Lannoo., 2007)
De Decker, Koen
boek